A critical analysis of the implementation of social networking as an e-recruitment tool within a security enterprise - Anthony Lewis; Brychan Thomas; Sophie James (Cogent Business & Management, 2015)
Many enterprises are operating in complex and competitive environments, and changes in the internal and external environment have prompted them to engage in better ways of doing business. In order to respond to these changes, and survive in today's volatile business environment, enterprises need to change their strategies. Human Resource departments are under pressure to keep operating costs low whilst also ensuring they are attracting, recruiting, and retaining talent within the enterprise. To achieve this, an increasing number of enterprises have adopted social networking into their recruitment strategy. This research aims to critically analyze the implementation of social networking as an e-recruitment tool within a Security Enterprise. The research key objective is to examine the importance of attracting Generation Y through the use of social networking sites and also to develop an understanding of the advantages and disadvantages of using social networking as an e-recruitment tool. The research also looks at contemporary examples of enterprises that have implemented social networking into their recruitment strategy. A further objective of the research is to gain an understanding of the attitudes and perceptions of the use of social networking as an e-recruitment tool. To achieve this, the research has taken a mixed-methods approach whilst focusing on an interpretivist stance. Data was gathered through an interview with the HR Manager at the Security Enterprise and a questionnaire was distributed to 22 employees within the enterprise and 84 respondents on social networking sites. The overall attitudes and perceptions of respondents showed that social networking can be effectively used as an e-recruitment tool as long as a traditional recruitment method is also used.
Keywords: 650